Knowledge and attitude of employees towards noise pollution in latex glove manufacturing industry / Ngam Kai Sien - Ngam , Kai Sien (2021)
The aim of this study was to determine employees’ knowledge and attitude towards noise pollution in latex glove manufacturing industry. A cross-sectional study was conducted involving 100 employees from latex glove manufacturing plant located at Meru, Klang. Questionnaire survey were being distributed among the 100 respondents to retrieve the socio-demography, working profile, knowledge, and attitude towards noise pollution. It was found that only 32% of the total respondents have passed the knowledge test from the questionnaire survey mainly due to the education level of the respondents. Some of the weak areas in terms of knowledge are the prevention knowledge and cause of NIHL knowledge. Besides that, the results also shows that overall mean score of the respondents’ attitude is 64.18%, which is higher when compared to the mean score of knowledge (43.62%) due to proper enforcement and effective practical training by the employers. However, some of the weak areas for the overall respondents in terms of attitude towards noise pollution is their health seeking attitude and risk-taking attitude. Lastly, it was found that the nationality, education level and the department of the employees will affect how well is their knowledge and their attitude towards noise pollution. These data were proven significance difference by conducting one way ANOVA analysis using SPSS Software. It is very crucial to have theoretical educational programmes on general prospects of noise pollution and prevention of noise induced hearing loss to the employees to further improve their awareness towards noise pollution.